Chemical hazards in industry. (Royal Society of Chemistry, 1984)
Monthly. English and foreign-language references to journal articles, books, audiovisuals materials, and conferences; intended for all personnel interested in health and safety management. Sources of references are about 200 journals manually scanned as well as peripheral sources. Arranged according to chemical hazards, biological hazards, precautions and legislation, and general. Each entry gives bibliographical information and abstract. Chemical and subject indexes.